1989
DOI: 10.1017/s0308210500018680
|View full text |Cite
|
Sign up to set email alerts
|

On subordinacy and analysis of the spectrum of Schrödinger operators with two singular endpoints

Abstract: SynopsisThe theory of subordinacy is extended to all one-dimensional Schrödinger operatorsfor which the corresponding differential expressionL= –d2/(dr2) +V(r) is in the limit point case at both ends of an interval (a,b), withV(r) locally integrable. This enables a detailed classification of the absolutely continuous and singular spectra to be established in terms of the relative asymptotic behaviour of solutions ofLu = xu, x εℝ, asr→aandr→b. The result provides a rigorous but straightforward method of direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 19 publications
0
87
0
Order By: Relevance
“…The contents of this section clearly has its origin in the beautiful theory of Gilbert and Pearson [120] which is known as the principle of subordinacy. This theory has since then been simplified and extended by various people (see e.g., [119], [48], [145]). I follow ideas of [68], [139], [163], and [207].…”
Section: Notes On Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The contents of this section clearly has its origin in the beautiful theory of Gilbert and Pearson [120] which is known as the principle of subordinacy. This theory has since then been simplified and extended by various people (see e.g., [119], [48], [145]). I follow ideas of [68], [139], [163], and [207].…”
Section: Notes On Literaturementioning
confidence: 99%
“…The results stated in this appendix are collected from [16], [17], [68], [73], [119], [198], [199], [200], [202], [203], [206]. In this chapter an important role will be played by Borel measures ρ on R. Hence we fix some notation first.…”
Section: Herglotz Functionsmentioning
confidence: 99%
“…Then Σ ±,n,sc and Σ sc are minimal supports (cf., e.g., [4], [21], [22], [32], [33]) of dν ±,n,sc and dν tr sc , where dν tr = dν 1,1 + dν 2,2 abbreviates the trace measure of the 2×2 matrix-valued spectral measure dν p,q , 1 ≤ p, q ≤ 2 of H (derived from g(z, n 0 ), g(z, n 0 + 1), h(z, n 0 ), cf. (2.12)-(2.14)).…”
Section: Taking Into Account (326)-(329)mentioning
confidence: 99%
“…It is a natural extension of the Gilbert-Pearson theory of subordinacy [5,6], and it allows us to analyze the dimensional Hausdorff properties for a number of examples with the singular-continuous spectrum. Below we describe the main ideas of our study and some of the main results.…”
mentioning
confidence: 99%
“…The spectral measures of a line operator can be constructed from those of corresponding two half-line operators (a left and a right), and while the relations are not completely trivial, they do allow an extension of the subordinacy theory to this case. Gilbert [6] has shown that the absolutely continuous part of the spectral measures of a line operator is supported on the set of energies for which at least one of the half-line problems has no subordinate solution. The singular part is supported on the set of energies for which (5) has a solution which is subordinate both to the right and to the left.…”
mentioning
confidence: 99%